Lady Tremaine : a novel - Hochhauser, Rachel (Reese's book club., 2026)
"Twice-widowed, Lady Etheldreda Verity Isolde Tremaine Bramley is solely responsible for her two children, a priggish stepdaughter, a razor-taloned peregrine falcon, and a crumbling manor. Fierce and determined, Ethel clings to the respectability her deceased husband's title affords her, hoping it will secure her daughters' future through marriage. When a royal ball offers the chance to change everything, Ethel risks her pride in pursuit of an invitation for all three of her daughters--only to see her hopes fulfilled by the wrong one. As an engagement to the future king unfolds, Ethel discovers a sordid secret hidden in the depths of the royal family, forcing her to choose between the security she craves and the wellbeing of the stepdaughter who has rebuffed her at every turn. As if Bridgerton met Circe, and exhilarating to its core, Lady Tremaine reimagines the myth of the evil stepmother at the heart of the world's most famous fairy tale. It is a battle cry for a mother's love for her daughters, and a celebration of women everywhere who make their own fortunes"-- Provided by publisher.